Strategy deployment using balanced scorecards. (15th November 2004) - Pyzdek, Thomas
There is often a disconnect between some organisations' goals and their strategies and plans for achieving them. In such organisations goals are little more than wishes and hopes and organisational actions tend to maintain the status quo. Improvement activities, to the extent if they exist at all, tend to be sporadic, local, and unfocused. Strategic results of improvement activities are usually disappointing, if measured at all. This article describes an approach that shows how goals can be used to drive strategy and linked directly to action. Although Six Sigma is used to illustrate the approach, it can be used by any organisation interested in improving itself. The approach has been used by the author to help leaders deploy their strategies in many industries, including high and low volume manufacturing as well as services and software.